2020
DOI: 10.5395/rde.2020.45.e19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic cleaning on the bond strength of fiber posts in oval canals filled with a premixed bioceramic root canal sealer

Abstract: Objective: This study aimed to evaluate the effect of ultrasonic cleaning of the intracanal post space on the bond strength of fiber posts in oval canals filled with a premixed bioceramic (Bio-C Sealer [BIOC]) root canal sealer. Materials and Methods: Fifty premolars were endodontically prepared and divided into 5 groups (n = 10), based on the type of root canal filling material used and the post space cleaning protocol. A1: gutta-percha + AH Plus (AHP) and post space preparation with ultrasonic cleaning, A2: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Although these effects are desirable from an endodontic point of view, this kind of bond and the tubule penetration reached by these materials might interfere in the future restoration of the teeth. Vilas-Boas et al ( 14 ) and Peña Bengoa et al ( 15 ) reported a reduction of the bond strength of fiber posts in teeth filled with bioceramic sealers. They attributed these lower values to the high tubule penetration and the difficulty of removing this type of material from the canal walls.…”
Section: Introductionmentioning
confidence: 99%
“…Although these effects are desirable from an endodontic point of view, this kind of bond and the tubule penetration reached by these materials might interfere in the future restoration of the teeth. Vilas-Boas et al ( 14 ) and Peña Bengoa et al ( 15 ) reported a reduction of the bond strength of fiber posts in teeth filled with bioceramic sealers. They attributed these lower values to the high tubule penetration and the difficulty of removing this type of material from the canal walls.…”
Section: Introductionmentioning
confidence: 99%
“…These obstructed dentinal tubules, interfere with the formation of a hybrid layer of resin cement ,subsequently, reducing the post bond strength. (5) Bengoa et al (6) confirmed the importance of endodontic sealer assessment before using in a tooth that will be restored with a fiber post.…”
Section: Introductionmentioning
confidence: 95%
“…14,15,16 Neither of these strategies has been studied at length in regard to irrigant activation in the root canal after PSP, but both have been shown to improve debris removal and bond strength of fiber posts. 3,10,16 The effect of EC used in continuous rotation was observed for debris removal from the main canal and the isthmus of the mesial root of mandibular molars, and was found to be adequate. 17,18 However, no studies have investigated the effect of EC under low-speed continuous rotation as a post space irrigation (PSI) strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Post space preparation (PSP) leads to the formation of a smear layer that contains the residual filling material used to fill the root canal, 1,2 and this layer on the root canal wall may influence the retention of fiberglass posts. 3 Considering that the adhesive failure of fiberglass posts is mainly related to debonding at the resin cement/dentin interface, [2][3][4][5] the residual filling material bonded to the canal walls should be removed to improve fiberglass post retention. 3,6 Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation